Pengaruh Latihan Plyometric High-intensity Interval Training terhadap Sistem Kardiovaskular Wanita Dewasa: Pengukuran menggunakan Polar H-10 dan Elite HRV - Andi Susilo, Eko; Imawati, Veni; Febriansyah, Afdol (Universitas Nahdlatul Ulama Blitar, 2025)
The aim of this study was to examine plyometrics-HIIT training on HRV in sedentary adult women. Participants were 30 adult women divided into two groups: plyometrics-HIIT treatment group (n= 15, age= 33±0.9 years, BMI= 20.8±1.0 kg/m2) and control group (n= 15, age= 31±0.7 years, BMI= 20.2±0.9 kg/m2). The treatment group was given plyometrics-HIIT training for six weeks. Heart Rate Variability (HRV) was measured using Polar H-10 and Elite-HRV app 24-48 hours before training and 24 hours after training. Independent sample t-tests were used to determine differences between the baseline characteristics of the two groups using two-way repeated measures ANOVA. All statistical tests were performed with IBM SPSS version 26. In the treatment group, the time domain was significantly improved at (SDNN; 45.78±46.20 vs 64.35±44.50 ms, p<0.05, RMSSD; 49.52±58.07 vs 77.62±61.18 ms, p<0.05). HRrest decreased significantly after exercise (78.84±18.5 vs 67.5±15.8 bpm, p<0.05). However, there were no significant differences in all frequency domain measurements. In conclusion this study plyometric-HIIT can improve cardiovascular function in underactive adult women. Thus, plyometric-HIIT can be assessed as an alternative exercise to reduce the risk of cardiovascular disease.